Innovative use of Barley Straw to control algal blooms and improve wastewater quality: Microbial community insights in a sustainable pre-filtration conditioning - Atef Mohamed Gad Mohamed; Ashraf Ahmed; Eman A. Mahmoud; Eman M. Farahat; Khaled N.M. Elsayed; Abeer El Shahawy (Ecological Engineering, 2026)

CD38-driven NAD⁺ depletion governs crypt structure and barrier dysfunction in fluorouracil-induced colonic mucositis: From metabolic collapse to architectural remodeling - Elsayed A. Elmorsy; Rabab S. Hamad; Mohammed Alorini; Attia M. Gabr; Hamad Alsaykhan; Mostafa M. Khodeir; Mohamed F. Hindawy; Abdulaziz A. Alsalloom; Eman Mohamad El Nashar; Ahmed G. Hamad; Haytham Ali; Mohammed Ashraf Ali; et al. (Tissue and Cell, 2026)

Growth, Digestive Enzyme Activities, Antioxidant Properties, and Intestinal Histology of Nile Tilapia ( Oreochromis niloticus ) Fed Diets Supplemented With Garlic Nanoparticles - Sami Alaa Sami; Ashraf Y. El‐Dakar; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Mohammed F. El Basuini; Shymaa M. Shalaby; Mohamed M. Rashad; Simon J. Davies; Mohamed F. Abdel‐Aziz (New Zealand Journal of Marine and Freshwater Research, 2026)
This work may be the first of its kind to assess the effects of varying inclusion levels of garlic nanoparticles (NPsG) as feed additives on growth and physiological indices in Nile tilapia ( Oreochromis niloticus ). Garlic contains an organosulfur compound called allicin that can promote growth and strengthen the immune system by stimulating appetite and the intestinal flora, thus enhancing energy utilization. Nanotechnology provides new tools in aquaculture nutrition, including increasing the ability of fish to absorb nutrients rapidly and the effectiveness of feed additives by enhancing their bioavailability compared to their bulk form. Five concentrations of NPsG (0, 150, 300, 600, or 1200 mg/kg) were evaluated by their addition to a basal diet (30% crude protein). 225 juveniles with an initial weight of 3.92 g ± 0.42 (SE) were randomly divided into 15 cages of polyethylene. The cage had dimensions of length: width: height (100:40:60 cm) and was continuously aerated using a 2 HP air blower with air stones. After 42 days, feeding results revealed that NPsG supplementation had significant effects ( p < 0.05) on improving the performance, physiological indicators, and histomorphometry of the intestine in comparison with the control. Fish that were fed a dietary supplement of 600 mg/kg of NPsG exhibited the highest specific growth rate (2.80%/day), along with elevated levels of intestinal enzymes lipase, amylase, and proteases (212.40, 15.00, and 318.60 U/g of intestine, respectively) and the lowest malondialdehyde level (81 nmol/g of liver tissue). This group was followed by fish fed a diet of 300 mg/kg of NPsG, which did not significantly differ from those fed 600 mg/kg of NPsG in superoxide dismutase, total antioxidant capacity, and histomorphometry of intestine villi. Finally, the complete dose–response recommendation (benefit at 300–600 mg/kg and detriment at 1200).

Mechanistic Insights into Honey-Mediated Antibacterial Activity Against Enterobacteriaceae: A Multifaceted Approach Targeting Membrane Integrity, Protein Synthesis, and Quorum Sensing Inhibition - Mervat G. Hassan; Naseh A. Algehainy; Batul Hatem Ghoniem; Faisal H. Altemani; Ashraf Elsayed; Hanaa Ghabban; Alaa Elmetwalli (Probiotics and Antimicrobial Proteins, 2026)

Wound healing potential by scratch assay and new flavone glycoside of Jacaranda ovalifolia R. Br. flowers - Sara Abd-Eltawab Makhlouf Mohammad; Miada Fouad Abdelwahab; Mamdouh Nabil Samy; Katsuyoshi Matsunami; Ashraf Nageeb Elsayed Hamed (South African Journal of Botany, 2026)

Insights into the stomach of tiger shark, Galeocerdo cuvier (Péron & Lesueur, 1822): Histochemical, ultrastructural, and phylogenetic analysis - Fatma A. Madkour; Elsayed S.I. Mohammed; Eman E. El-Nahass; Mona M. Elwan; Ashraf S. Mohammad; Fatma Abdelhakeem (Tissue and Cell, 2026)

The impact of heavy metal pollution: bioaccumulation, oxidative stress, and histopathological alterations in fish across diverse habitats - Eman Zahran; Al-Zahraa Mamdouh; Samia Elbahnaswy; Mai M. A. El-Son; Engy Risha; Ashraf ElSayed; Manal Ibrahim El Barbary; Mahmoud G. El Sebaei (Aquaculture International, 2025)
Heavy metal contamination of aquatic environments threatens fish health and ecosystems. This review examines the bioaccumulation patterns, toxicity mechanisms, effects of oxidative stress, and histopathological changes induced by heavy metals in various fish species across different habitats. Important heavy metals, including mercury, cadmium, lead, arsenic, chromium, copper, and iron, are discussed. These metals can bioaccumulate in fish tissues via waterborne and dietary exposure, and bioaccumulation depends on several factors such as metal type, fish species, and exposure conditions. The generation of reactive oxygen species is one of the main reasons why heavy metals exert their toxic effects; depletion of antioxidants and damage to cellular components lead to oxidative stress. Oxidative stress is induced by alterations in antioxidant enzymes and increases in lipid peroxidation levels. Histopathological changes were recorded in target organs, such as the gills, liver, and kidneys. We emphasize the existing knowledge gap, which requires further research to provide full insights into fish heavy metal toxicity, with potential implications for human consumers. Understanding the toxicity mechanisms of heavy metals in fish is the key to developing biomarkers and mitigation strategies to protect aquatic ecosystems.

The Role of MicroRNAs in Neurodegeneration: Insights from Huntington’s Disease - Reda M. Mansour; Abanoub A. S. Shaker; Ahmed I. Abulsoud; Sherif S. Abdel Mageed; Alaa Ashraf; Elsayed G. E. Elsakka; Mohammed. I. Dahab; Mohamed M. Sadek; Farah A. Awad; Radwa H. Lutfy; Hanan Elimam; Ahmed H. I. Faraag; et al. (Molecular Neurobiology, 2025)

Harnessing the power of miRNAs for precision diagnosis and treatment of male infertility - Ahmed S. Doghish; Elsayed G. E. Elsakka; Hebatallah Ahmed Mohamed Moustafa; Alaa Ashraf; Sherif S. Abdel Mageed; Osama A. Mohammed; Mustafa Ahmed Abdel-Reheim; Mohamed Bakr Zaki; Hanan Elimam; Nehal I. Rizk; Sarah A. Omran; Shimaa A. Farag; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Low stress drop and strike-slip detachment faulting: insights from a new earthquake sequence in the El-Nuqra Region, Southeastern Desert, Egypt - Hamada Saadalla; Saleh Qaysi; Abdelnasser Mohamed; Elsayed Issawy; Lucia Fojtikova; Eman Abu-Nadr; Ashraf Adly; Mohamed Ezzalarab (Modeling Earth Systems and Environment, 2025)

Enhanced resistance of Vigna unguiculata to Fusarium oxysporum via Rubia cordifolia extract and growth-promoting endophytic Bacillus amyloliquefaciens DW6 - Abeer A. Ghoniem; Khaled M. Elattar; Amenah S. Alotaibi; Hanaa Ghabban; Mohammed S. El Hersh; Ayman Y. El-Khateeb; Yasser A. El-Amier; Hala M. El-Gendy; Noha M. Eldadamony; WesamEldin I. A. Saber; Ashraf Elsayed (European Journal of Plant Pathology, 2024)

Efficient adsorption of fluorescein dye from aqueous solutions by Al/Th-MOF bimetal-organic frameworks: Adsorption isotherm, kinetics, DFT computation, and optimization via Box-Behnken design - Nawaa Ali H. Alshammari; Jawza Sh Alnawmasi; Alya M. Alotaibi; Odeh A.O. Alshammari; May Abdullah Abomuti; Nadia H. Elsayed; Ashraf A. El-Bindary (Process Safety and Environmental Protection, 2024)

Durable graphene-based alkyd nanocomposites for surface coating applications - Mohamed S. Selim; Abdelaziz N. El-hoshoudy; ElSayed G. Zaki; Ashraf M. EL-Saeed; Ahmed A. Farag (Environmental Science and Pollution Research, 2024)
Recently, the scientific community’s main goal is the long-term sustainability. Vegetable oils are easily accessible, non-depletable, and cost-effective materials. Vegetable oils are used to prepare polymeric alkyd surfaces. Novel and exciting designs of alkyd/graphene nanocomposites have provided eco-friendly thermal stability and protective coating surfaces. This review has briefly described important graphene-based alkyd nanocomposites along with their applications as protective coatings. These alkyd composites have high hydrophobicity, corrosion resistance, and durability. Graphene-based alkyd nanocoatings have many industrial and research interests because of their exceptional thermal and chemical properties. This work introduces an advanced horizon for developing protective nanocomposite coatings. The anti-corrosion properties and coatings’ longevity may be improved by combining the synergistic effects of hybrid nanofillers introduced in this work.

Phenotypic and genotypic characterization of resistance and virulence in Pseudomonas aeruginosa isolated from poultry farms in Egypt using whole genome sequencing - Amira M. Rizk; Marwa M. Elsayed; Ashraf A. Abd El Tawab; Fatma I. Elhofy; Enas A. Soliman; Tamara Kozytska; Hanka Brangsch; Lisa D. Sprague; Heinrich Neubauer; Gamal Wareth (Veterinary Microbiology, 2024)

Antioxidant and anti-inflammatory potential of spirulina and thymoquinone mitigate the methotrexate-induced neurotoxicity - Alaa Behairy; Ashraf Elkomy; Faten Elsayed; Mohamed M. S. Gaballa; Ahmed Soliman; Mohamed Aboubakr (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
The objective of this study was to investigate whether the neurotoxic effects caused by methotrexate (MTX), a frequently used chemotherapy drug, could be improved by administering Spirulina platensis (SP) and/or thymoquinone (TQ). Seven groups of seven rats were assigned randomly for duration of 21 days. The groups consisted of a control group that was given saline only. The second group was given 500 mg/kg of SP orally; the third group was given 10 mg/kg of TQ orally. The fourth group was given a single IP dose of 20 mg/kg of MTX on the 15 th day of the experiment. The fifth group was given both SP and MTX, the sixth group was given both TQ and MTX, and the seventh group was given SP, TQ, and MTX. After MTX exposure, the study found that AChE inhibition, depletion of glutathione, and increased levels of MDA occurred. MTX also decreased the activity of SOD and CAT, as well as the levels of inflammatory mediators such as IL-1, IL-6, and tumor necrosis factor-α. MTX induced apoptosis in brain tissue. However, when MTX was combined with either SP or TQ, the harmful effects on the body were significantly reduced. This combination treatment resulted in a faster return to normal levels of biochemical, oxidative markers, inflammatory responses, and cell death. In conclusion, supplementation with SP or TQ could potentially alleviate MTX-induced neuronal injury, likely due to their antioxidant, anti-inflammatory, and anti-apoptotic effects.

Isolation and structural characterization of phytoconstituents from leaves of Bignonia binata - Mamdouh Nabil Samy; Basma Khalaf Mahmoud; Ashraf Nageeb Elsayed Hamed; Sachiko Sugimoto; Katsuyoshi Matsunami; Mohamed Salah Kamel (Natural Product Research, 2024)

Evaluation and performance comparison of different models for global solar radiation forecasting: a case study on five cities - Mohamed A. Ali; Ashraf Elsayed; Islam Elkabani; M. Elsayed Youssef; Gasser E. Hassan (Environment, Development and Sustainability, 2023)
Recently, solar energy has emerged as the most promising renewable energy source to meet the world’s energy demands. However, to harness the potential of solar energy, accurate data on solar radiation are crucial. It is considered the first step in assessing solar resources for various applications and achieving energy sustainability goals. Due to the unavailability of solar radiation measurements in many parts of the world, several models have been developed to predict global solar radiation (GSR) at these locations. Thus, this study aims to evaluate the proficiency of several GSR models at five new locations and determine the most suitable one for GSR prediction. The study has further developed solar radiation models for these new locations, as well as general ones for the entire region, which does not have any GSR models despite the existence of many planned solar energy facilities in this area. Additionally, the study investigates the effect of changing the length of the validation dataset on models’ performance and accuracy, as well as assesses the introduced models’ generalization capability. To achieve these objectives, the observed data of GSR for approximately 37 years at studied locations are used to develop and validate the proposed models. The study’s findings reveal that Model 1 provides the best performance at all locations, with accuracy, coefficient of determination ( $$R^{2}$$ R 2 ), ranging from 95 to 98%, except for the coastal location, where it is from 91 to 95%. The remaining performance indicators of the best models, such as RMSE, MABE, MAPE, and $$r$$ r , are good, and their values range from 0.7863 to 1.9097 (MJ m −2 day −1 ), from 0.6430 to 1.7060 (MJ m −2 day −1 ), from 3.4319 to 10.0890 (%), and from 0.9914 to 0.9981, respectively. The length of the validation dataset has a slight effect on the models’ performance, ranging from about 1% to 2%. Therefore, Model 1 is the recommended solar radiation model, which can provide precise and rapid estimates of global solar radiation. This approach could be used in the design and performance evaluation of many solar applications. The primary benefit of this approach in the current investigation is that temperature data are continuously and effortlessly recorded for various purposes.

Machado-Joseph disease in a Sudanese family links East Africa to Portuguese families and allows reestimation of ancestral age of the Machado lineage - Sandra Martins; Ashraf Yahia; Inês P. D. Costa; Hassab E. Siddig; Rayan Abubaker; Mahmoud Koko; Marc Corral-Juan; Antoni Matilla-Dueñas; Alexis Brice; Alexandra Durr; Eric Leguern; Laura P. W. Ranum; et al. (Human Genetics, 2023)
Machado-Joseph disease (MJD/SCA3) is the most frequent dominant ataxia worldwide. It is caused by a (CAG) n expansion. MJD has two major ancestral backgrounds: the Machado lineage, found mainly in Portuguese families; and the Joseph lineage, present in all five continents, probably originating in Asia. MJD has been described in a few African and African-American families, but here we report the first diagnosed in Sudan to our knowledge. The proband presented with gait ataxia at age 24; followed by muscle cramps and spasticity, and dysarthria, by age 26; he was wheel-chair bound at 29 years of age. His brother had gait problems from age 20 years and, by age 21, lost the ability to run, showed dysarthria and muscle cramps. To assess the mutational origin of this family, we genotyped 30 SNPs and 7 STRs flanking the ATXN3 _CAG repeat in three siblings and the non-transmitting father. We compared the MJD haplotype segregating in the family with our cohort of MJD families from diverse populations. Unlike all other known families of African origin, the Machado lineage was observed in Sudan, being shared with 86 Portuguese, 2 Spanish and 2 North-American families. The STR-based haplotype of Sudanese patients, however, was distinct, being four steps (2 STR mutations and 2 recombinations) away from the founder haplotype shared by 47 families, all of Portuguese extraction. Based on the phylogenetic network constructed with all MJD families of the Machado lineage, we estimated a common ancestry at 3211 ± 693 years ago.

Metabolic profiling and cytotoxic activities of ethanol extract of Dypsis leptocheilos aerial parts and its green synthesized silver nanoparticles supported by network pharmacology analysis - Marwa Hassan Hussaen Mohammed; Ashraf Nageeb Elsayed Hamed; Sammar Fathy Elhabal; Fatma A. Mokhtar; Usama Ramadan Abdelmohsen; Mostafa Ahmed Fouad; Mohamed Salah Kamel (South African Journal of Botany, 2023)

Narcissus pseudonarcissus L. (Amaryllidaceae) bulb metabolite profiling and biological activities - Youstina Refaat Boshra; Eman Zekry Attia; Ahmed G. Darwish; Maria Refaat Boshra; Mohamed N. Amin; Ashraf Nageeb Elsayed Hamed; Samar Yehia Desoukey; John Refaat Fahim (South African Journal of Botany, 2023)

Wound healing potential of Narcissus pseudonarcissus L. bulbs supported with chemical and molecular docking investigations - Youstina Refaat Boshra; Yaser A. Mostafa; Ashraf Nageeb Elsayed Hamed; Samar Yehia Desoukey; John Refaat Fahim (South African Journal of Botany, 2023)

Chemical composition and anti-proliferative activities of Hyophorbe lagenicaulis aerial parts and their biogenic nanoparticles supported by network pharmacology study - Marwa Hassan Hussaen Mohammed; Ashraf Nageeb Elsayed Hamed; Sammar Fathy Elhabal; Fatma A. Mokhtar; Usama Ramadan Abdelmohsen; Mostafa Ahmed Fouad; Mohamed Salah Kamel (South African Journal of Botany, 2023)

How can imported monkeypox break the borders? A rapid systematic review - Ramy Mohamed Ghazy; Elsayed Mohamed Hammad; Mohamed Ashraf Hall; Amira Mahboob; Sally Zeina; Eman H. Elbanna; Noha Fadl; Shaimaa Abdelaziz Abdelmoneim; Rony ElMakhzangy; Hammad Mohamed Hammad; Afrah humidan Suliman; Hayat Hasab Alkreem Atia; et al. (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Evaluation of the antineoplastic property of prodigiosins and 5-fluorouracil in restraining the growth of Ehrlich solid tumors in mice - Elsayed S. E. Hassan; Medhat W. Shafaa; Ahmed H. I. Faraag; Ehab Essawy; Ashraf A. Bakkar; Wafa A. AL-Megrin; Manal F. El-Khadragy; Mohamed S. Abdelfattah; Ahmed E. Abdel Moneim (Environmental Science and Pollution Research, 2022)

Aerodynamics of ancient egyptian Obelisks and their structural response to Boundary Layer wind - Ahmed ElDegwy; Ashraf Elsayed; Mohamed Darwish (Environmental Fluid Mechanics, 2022)
Ancient Egyptian obelisks have been carved thousands of years ago and survived many earthquakes and wind storms. This study examines the aerodynamic characteristics and the response of two of the tallest and slenderest ancient Egyptian obelisks to boundary layer winds using a two-phase methodology. The firstphase involved preparing computational fluid dynamics (CFD) models for the twoobelisks with different angles of projection to wind. The variations in the windpressure coefficient and the forces on the obelisks have been studied for differentprojection angles, different reference velocities and along the height of eachobelisk. Within the second phase structural analysis was performed subjecting eachobelisk to a wind load under different angles of loading. The results show that whensubject to boundary layer winds, the pressure coefficient on the surface and thestresses within the obelisks vary significantly with the angle of attack and dimensions of the obelisk.

Characterization and Expression Analysis of Extradiol and Intradiol Dioxygenase of Phenol-Degrading Haloalkaliphilic Bacterial Isolates - Nasser H. Abbas; Afaf Elsayed; Hamdy A. Hassan; Sabha El-Sabbagh; Ashraf F. Elbaz; Hany Khalil (Current Microbiology, 2022)
Haloalkophilic bacteria have a potential advantage as a bioremediation organism of high oil-polluted and industrial wastewater. In the current study, Haloalkaliphilic isolates were obtained from Hamralake, Wadi EL-Natrun, Egypt. The phenotype script, biochemical characters, and sequence analysis of bacterial-16S rRNA were used to identify the bacterial isolates; Halomonas HA1 and Marinobacter HA2 . These strains required high concentrations of NaCl to ensure bacterial growth, especially Halomonas HA1 strain. Notably, both isolates can degrade phenol at optimal pH values, between 8 and 9, with the ability to grow in pH levels up to 11, like what was seen in the Halomonas HA1 strain. Moreover, both isolates represent two different mechanistic pathways for phenol degradation. Halomonas HA1 exploits the 1,2 phenol meta-cleavage pathway, while Marinobacter HA2 uses the 2,3 ortho-cleavage pathway as indicated by universal primers for 1,2 and 2,3 CTD genes. Interestingly, Marinobacter HA2 isolate eliminated the added phenol within an incubation period of 72 h, while the Halomonas HA1 isolate invested 96 h in degrading 84% of the same amount of phenol. Phylogenetic analysis of these 1,2 CTD (catechol dioxygenase) sequences clearly showed an evolutionary relationship between 1,2 dioxygenases of both Halomonadaceae and Pseudomonadaceae . In comparison, 2,3 CTD of Marinobacter HA2 shared the main domains of the closely related species. Furthermore, semi-quantitative RT-PCR analysis proved the constitutive expression pattern of both dioxygenase genes. These findings provide new isolates of Halomonas sp. and Marinobacter sp. that can degrade phenol at high salt and pH conditions via two independent mechanisms.

Testicular toxicity of cisplatin in rats: ameliorative effect of lycopene and N-acetylcysteine - Asmaa Elsayed; Ashraf Elkomy; Mohamed Alkafafy; Reda Elkammar; Anwar El-Shafey; Ahmed Soliman; Mohamed Aboubakr (Environmental Science and Pollution Research, 2022)

LC-MS-based identification of bioactive compounds and hepatoprotective and nephroprotective activities of Bignonia binata leaves against carbon tetrachloride-induced injury in rats - Mamdouh Nabil Samy; Ashraf Nageeb Elsayed Hamed; Basma Khalaf Mahmoud; Eman Zekry Attia; Usama Ramadan Abdelmohsen; Michael Atef Fawzy; Mina Ezzat Attya; Mohamed Salah Kamel (Natural Product Research, 2022)

Metabolomic profiling and biological investigation of Tabebuia Aurea (Silva Manso) leaves, family Bignoniaceae - Basma Khalaf Mahmoud; Ashraf Nageeb Elsayed Hamed; Mamdouh Nabil Samy; Usama Ramadan Abdelmohsen; Eman Zekry Attia; Michael Atef Fawzy; Rana Hosny Refaey; Mohammad Alaraby Salem; Sheila Marie Pimentel-Elardo; Justin R. Nodwell; Samar Yehia Desoukey; Mohamed Salah Kamel (Natural Product Research, 2021)

Gymnothorax spp. (Muraenidae) as natural predators of the lionfish Pterois miles in its native biogeographical range - Arthur R. Bos; Ashraf M. Sanad; Khamis Elsayed (Environmental Biology of Fishes, 2017)

A simple real-time polymerase chain reaction assay using SYBR Green for hepatitis C virus genotyping - Hosam Zaghloul; A. A. El Morsi; H. E. Soweha; Ashraf Elsayed; S. Seif; Hossam El-Sharawy (Archives of Virology, 2017)

Low frequency paternal transmission of plastid genes in Brassicaceae - Anja Schneider; Christian Stelljes; Caroline Adams; Stefan Kirchner; Gabi Burkhard; Sabine Jarzombski; Inge Broer; Patricia Horn; Ashraf Elsayed; Peter Hagl; Dario Leister; Hans-Ulrich Koop (Transgenic Research, 2015)